Comportamento de vacas leiteiras da raça holandesa, em pastagem de milheto com e sem sombra - Rossarolla, Grasiela (2007)
Aiming at evaluating the daily basis total amount of time of the main dairy cows activities in grazing land, and to define the adequate time sessions to the dairy cows behavior check and to evaluate the shade availability influence in grazing land areas in physiologic responses of dairy cows. An experiment was conducted at UFSM Bovine laboratory of the Animal Science Department RS with 18 dairy cows. The experiment was composed by two treatments: artificial shading (six m2/cow) and no shading. The ruminant-forage systems herbage allowance was estimated through millet (Pennisetum americanum) ruminant-forage availability estimations, made at the beginning of each period of behavioral evaluation. Four evaluation periods were conducted, at a total of 20 daily hours, being observed, every 5 minutes (morning period) and every 10 minutes (night period), the occurrence of grazing activity, rumination and steadiness. The different intervals of observation evaluated were: 5, 10, 15 and 20 minutes in the morning and 10 and 20 minutes at night. The physiological parameters evaluated were: rectal temperature (°C), respiratory frequency (mov/min) and heart Frequency (beats/min). The animals were distributed in a whole casual lining with 9 cows per treatment. The reduction in the offer of ruminant-forage increased the grazing time and the rumination diminished the steady period. The animals without access to the shade decrease the grazing time, without compensating that with night grazing. There was a difference in the grazing activity between the periods, considering that the cows have grazed more during the morning than during the night. The cows ruminated more at night, having no difference between the treatments, however during the day the cows with no shade available kept more time ruminating. For the animals with access to the shade this activity has been higher during the night, which did not differ from the treatment without access to the shade. The average morning time of grazing, rumination and leisure did not differ (P>0.05) for the different intervals used in the four observation periods. Animals without access to the artificial shade have rectal temperatures, respiratory frequency and cardiac frequency increased if compared to animals that had access to the shade